"I Learned How to Read in Spanish": A Genealogical Analysis of Biliterate Subjective Possibilities in South Texas Escuelitas and Beyond. Issue 6 (June 2022) - Degollado, Enrique David; Bell, Randy; Harvey-Torres, Rosalyn
Background/Context: Historically, the literature on access to quality education for Mexican Americans has been wrought with injustices committed on them because of the racist and deficit thinking of the time. This includes, but is not limited to, access to literacy in English and Spanish. This article focuses on las escuelitas, or little schools, as sites of resistance that fostered Spanish literacy as an extension of the home before official schooling in all English public schools. These little schools were community-based initiatives that taught Texas Mexican children Spanish literacy and Mexican culture from the late 1800s to the mid-1900s in the borderlands. Purpose/Objective/Research Question/Focus of Study: Drawing on nepantla and border thinking as theoretical frameworks, we argue that biliterate subjectivities emerge(d) from geographically contingent ideologies rooted in colonizing codes of power. We asked: (1) How do participants describe their early literacy experiences in las escuelitas? (2) How do the discursive characterizations of participants' early literacy experiences inform our understanding of emerging discursive biliterate subjectivities? Research Design: Employing a Foucauldian genealogical analysis, this article examines the experiences of nine escuelitas attendees. Oral histories were collected form a group of Mexican Americans who attended las escuelitas in the 1940s and were from the same graduating high school class, though they did not attend the same escuelita. Alongside their narratives, we draw on historical accounts of las escuelitas and broader Mexican American history of education of the southwestern United States. Other data include poems and textbooks provided by the participants themselves. Foucauldian genealogical analysis offered a more nuanced story in which to situate their narratives. Findings/Results: The findings demonstrate how biliterate subjectivities were produced ideologically as the participants lived and made meaning in a time when official biliteracy was not only inconceivable, but effectively outlawed by English-only laws governing public schools. We go on to consider the clandestine biliteracy of escuelita attendees of the early 20th century, in contrast to the growing popularity of official forms of biliteracy for (some) contemporary students in schools today. To do so, we detail how participants engaged in complex and contradictory discursive characterizations that revealed their nepantla and border thinking as a way of reading and writing the world. Thus, las escuelitas provide historical insight into not only the ingenuity of communities to resist English hegemony, but also how present-day bilingual education often reinscribes marginalization. Conclusions/Recommendations: The discursive narratives demonstrate the complexity of forming subjectivities in relation to biliteracy. We reveal the ways in which their biliterate subjectivities of reading the word informed the ways in which they also read the world. Thus, their subjective formations emanated nepantla and border thinking as a facet of their biliteracy. We also find that their biliteracy stories echo present discursive formations of who is considered biliterate through official manifestations like the Seal of Biliteracy. Finally, their stories indicate that biliteracy as a subjective possibility has always been rooted in communities of color whose lives and knowledges often go unrecognized.